Companies as responsible actors and corporate citizens - corporate criminal responsibility under the rule of law as a consequence - Dannecker, Gerhard; Schröder, Thomas (Organizational crime, 2023)
In the context of corporate criminal law, perpetrators seek to improve the company’s performance at the expense of individual third parties and the general public. These occurrences can partly be attributed to the inadequate structure of the current economic criminal law and its imbalance between the responsibility of individual persons on the one hand and legal persons on the other. This is just one of the reasons why legal scholars as well as many people in positions of political responsibility share the view that the current German system of corporate sanctions law suffers from serious shortcomings. This essay aims at contributing to the current lively discussion in Germany on reforming and tightening criminal sanctions against legal entities. This paper takes the position that the lawmaker ought to consult the efforts already developed in economic criminology to understand corporate wrongdoing. In particular, measures to counter the development and maintaining of criminal corporate cultures and the predominance of “useful illegality” seem necessary. These measures, however, should not be of a draconian nature. Rather, the rule of law (“Rechtsstaatlichkeit”) requires that corporate citizens be punished. This implies not only taking corporate wrongdoing seriously but also acknowledging fundamental procedural rights for the accused legal entities. Finally, the systematic effort of companies to adhere to law (“Compliance”) needs to be part of corporate sentencing guidelines.
Gesehen am 22.06.2023